Progressive coevolution of the yeast centromere and kinetochore - Helsen, Jana; Ramachandran, Kausthubh; Sherlock, Gavin; Dey, Gautam (Nature, 2025)
During mitosis, stable but dynamic interactions between centromere DNA and the kinetochore complex enable accurate and efficient chromosome segregation. Even though many proteins of the kinetochore are highly conserved1,2, centromeres are among the fastest evolving regions in a genome3,4, showing extensive variation even on short evolutionary timescales. Here we sought to understand how organisms evolve completely new sets of centromeres that still effectively engage with the kinetochore machinery by identifying and tracking thousands of centromeres across two major fungal clades, including more than 2,500 natural strain isolates and representing over 1,000 million years of evolution. We show that new centromeres spread progressively via drift and subsequent selection and that the kinetochore, which is evolving slowly in relative terms, appears to act as a filter to determine which new centromere variants are tolerated. Together, our findings provide insight into the evolutionary constraints and trajectories shaping centromere evolution.
Online veröffentlicht: 26. November 2025
Gesehen am 26.01.2026